Cognitive ability, gender, and well-being in school contexts: longitudinal evidence from Sweden - Boman, Björn; Wiberg, Marie (Frontiers in Psychology, 2024)
While well-being does generally constitute a moderate predictor of school achievement, research on the predictive validity of cognitive ability for well-being in school contexts remains scant. The current study analyzed longitudinal relations between cognitive ability measured at age 12 (Grade 6) and well-being measured at age 18 (Grade 12, valid N = 2705) in a Swedish sample, using several multivariate model techniques. The results indicate that cognitive ability was not a statistically significant predictor when several predictors were entered in a multiple regression model. However, gender was a significant covariate as girls and young women have a substantially lower degree of self-reported well-being. This casts light on the limitations of cognitive ability as a construct for some non-cognitive outcomes, at least in shorter and narrower spatial-temporal contexts.